THERAPEUTIC EFFICACY OF LEVONORGESTREL INTRAUTERINE SYSTEM AS AN ALTERNATIVE TO HYSTERECTOMY FOR MANAGEMENT OF HEAVY MENSTRUAL BLEEDING IN PERIMENOPAUSAL WOMEN - Dash, Sudershan; Mishra, Jagannath; Shankar Behera, Shashis; Rout, Subhashree (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This prospective observational study has been conducted to find out the efficacy and patient satisfaction of levonorgestrel intrauterine system (LNG-IUS), and it was compared with results of hysterectomy in perimenopausal Indian women with heavy menstrual bleeding (HMB). Methods: It was a prospective study conducted on 135 cases after taking consent. Patients were inserted with LNG-IUS, and the outcome in terms of further bleeding and quality of life was compared to that of hysterectomy. Results and Conclusion: Levonogestrol containing-IUS is a highly effective treatment of HMB in perimenopausal women. It is a safe, effective, and quality of life after treatment makes it a good alternative to hysterectomy for HMB.